LNCAROD is stabilized by m6A methylation and promotes cancer progression via forming a ternary complex with HSPA1A and YBX1 in head and neck squamous cell carcinoma. Issue 6 (13th April 2020) - Ban, Yuanyuan; Tan, Pingqing; Cai, Jing; Li, Junjun; Hu, Meng; Zhou, Ying; Mei, Yan; Tan, Yixin; Li, Xiaoling; Zeng, Zhaoyang; Xiong, Wei; Li, Guiyuan; et al.
Abstract : Head and neck squamous cell carcinoma (HNSCC) constitute approximately 4% of all cancers worldwide. In this study, we analyzed the expression profile of the long noncoding RNA (lncRNA) of 502 HNSCC patients from The Cancer Genome Atlas database. Among the differentially expressed lncRNAs between HNSCC and normal samples, LNCAROD is overexpressed in HNSCC and associated with advanced T stage and shortened overall survival. The N 6‐methyladenosine (m6A) modification mediated by METTL3 and METTL14 enhanced the stability of LNCAROD in HNSCC cells. Depletion of LNCAROD attenuated cell proliferation, mobility in vitro, and tumorigenicity in vivo, whereas overexpression of LNCAROD exerted opposite effects. LNCAROD is mainly distributed in nucleus and binds with YBX1 and HSPA1A proteins. Silencing either YBX1 or HSPA1A did not affect the level of LNCAROD. However, loss of LNCAROD led to shortened half‐life of YBX1 protein. Mechanistically, LNCAROD protected YBX1 from proteasomal degradation by facilitating YBX1‐HSPA1A protein–protein interaction. Depletion of HSPA1A in LNCAROD‐overexpressing cells resulted in accelerated proteasomal degradation of YBX1 protein. Moreover, re‐expression of Flag‐YBX1 in LNCAROD‐silenced cells rescued malignant behavior of HNSCC cells. Our study indicates that LNCAROD is an oncogenic lncRNA and dysregulation of m6A modification might account for aberrant expression of LNCAROD in HNSCC. LNCAROD acts as a scaffold for the interaction between YBX1 and HSPA1A, preventing proteasomal degradation of YBX1 in HNSCC cells. Abstract : Dysregulation of long noncoding RNAs (lncRNAs) is implicated in cancer development and progression. In this study, Ban et al . demonstrated that an oncogenic lncRNA, LNCAROD, is stabilized by m6A methylation and overexpressed in head and neck squamous cell carcinoma (HNSCC). LNCAROD forms a ternary complex with HSPA1A and YBX1, preventing proteasomal degradation of YBX1. This study provides a new paradigm of the mechanisms of lncRNAs in HNSCC development.